KAPASITAS MASYARAKAT DALAM MEREDUKSI RISIKO BANJIR LAHAR DINGIN DI KAWASAN PERMUKIMAN SUNGAI CODE KECAMATAN DANUREJAN, KOTA YOGYAKARTA - , TRI BUDIHARTO; , Dr. M. Pramono Hadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
floods that occurred during the rainy season has enormous destructive Lahar power and cause damage to the surrounding environment. Management to handling lahar flood is different than usual flood because of the characteristics of lahar flood is different from the characteristics of the usual flood. The purpose of this study is to determine differences in the spatial distribution of elements at risk, vulnerability of socioeconomic differences, economic, social system, and the physical building, and to know the effect of the capacity of community-based risk management can reduce the risk of lahar floods in the settlements along the Code River. This research approach quantitative qualitative research combined with the deductive method and the use of typology rationalistic. This research is focused on residential areas along the Code River in the Danurejan District with due consideration to the region have been affected lahar flood risk is quite large eruption of Merapi in 2010. The sample of 90 respondents drawn from the 5% of the population in proportion to the number of members of sub-populations that are differentiated into three zones based on the hazard of the region. . The results showed that there are differences in the spatial distribution of elements at risk and vulnerability in areas with low hazard classes, regions with moderate hazard class, as well as areas with high hazard class, as well as the effect of increasing levels of community capacity-based risk management can reduce the risk of lahar floods in the settlements along the Code River.